PENGARUH LINGKUNGAN KERJA DAN KELELAHAN KERJA TERHADAP EMPLOYEE ENGAGEMENT DENGAN KUALITAS KEHIDUPAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT Nusantara Infrastructure Tbk) - Muhammad Reihan, (2023)
This research uses a quantitative study aimed to examine the direct and indirect effects of the work environment and burnout on employee engagement through the quality of work life as an intervening variable. This study involves a sample of 65 employees at PT Nusantara Infrastructure Tbk with saturated sampling technique. The analytical techniques applied in this research include descriptive analysis and inferential analysis, with the software used is SmartPLS 3.0. Hypothesis testing obtains (1) The work environment has a positive and significant effect on employee engagement. (2) Burnout has a positive and significant effect on employee engagement. (3) The work environment has a positive and significant effect on the quality of work life. (4) Burnout has a negative and significant effect on the quality of work life. (5) The quality of work life has a positive and significant effect on employee engagement. (6) The work environment has a positive and significant effect on employee engagement through the quality of work life. (7) burnout has a negative and significant effect on employee engagement through the quality of work life.